Climate Change and Health Teenager’s Perceptions as a Basis for Interventions - Sulistyawati Sulistyawati; Izzatun Nisa (International Journal of Public Health Science (IJPHS), 2016)
Climate change is becoming a major issue around the globe with increasing impact on human health. Strategies aiming to address these climate change impacts are thus a necessity. Involving teenagers as agents of change is one way to promote necessary changes in attitudes and behaviors, in the community and our future society. This paper explores climate change perceptions among teenagers in order to formulate strategies that include them as agents in climate change adaptation addressing health. We did quick survey in 95 students, which are categorized as teenagers from a senior high school in Gunungkidul, Indonesia randomly enrolled as respondents in this research, but 15 of them dropped out due to the incompleteness of answer. A structured questionnaire was used to measure the teenagers’ perceptions about climate change and health. Based on this research respondents have had an intermediate understanding of the impact of climate change on human health. There were 65% of respondents stated that they felt the impact of climate change this time. However, the level of understanding varies with respect to disease. So that, it is highly recommended to improve the knowledge of teenagers about climate change and its consequences on human health by use mass media (TV, Radio and the internet) as media channels for interventions targeting teenagers.